Challenges That Students Face in Developing and Overcoming Listening Skill (In Teaching Arabic to Non-Native Speakers) - Dalia Abdelgawad (Şarkiyat Mecmuası)
Communication for the foreign learner’s speaking and listening skills in the language he is learning is influenced by a number of elements. A learning obstacle for him and a problem for the teacher to conquer. The major goal of this article is to assist the learner in overcoming it, becoming comfortable with it, or handling it, and using an acceptable way to address it. This article aims to present a set of challenges that both teachers and students face in developing listening skills and understanding listening in the context of teaching Arabic as a foreign language, as well as how to overcome them, through some suggested solutions that teachers and students can use in developing listening comprehension and developing awareness of listening instructions. Also raising the efficiency of the teacher in the listening class. Listening is a complex process in the field of foreign language instruction, and it is crucial in the development of a student’s skills in Arabic as a foreign language. Listeners understand by using both ascending (language knowledge) and descending (previous knowledge) processes. The teacher can help students develop suitable strategies for listening comprehension through a hands-on approach for teaching listening. Undoubtedly, knowing the context and purpose of the listening text remarkably reduces the burden of understanding and acquiring this skill over time with proper practices. This in turn helps them learn how to listen and develop their knowledge. To succeed in understanding and developing listening skills, use suitable cognitive and metacognitive strategies. Finally, by providing a practical grasp of these challenges and how to overcome them, this essay tries to explain some of these specifics regarding hearing and what makes listening difficult.